The protein family TcTASV-C is a novel Trypanosoma cruzi virulence factor secreted in extracellular vesicles by trypomastigotes and highly expressed in bloodstream forms - Caeiro, Lucas D.; Alba-Soto, Catalina D.; Rizzi, Mariana; Solana, María Elisa; Rodriguez, Giselle; Chidichimo, Agustina M.; Rodriguez, Matías E.; Sánchez, Daniel O.; Levy, Gabriela V.; Tekiel, Valeria (PLOS Neglected Tropical Diseases, 2018)
TcTASV-C is a protein family of about 15 members that is expressed only in the trypomastigote stage of Trypanosoma cruzi. We have previously shown that TcTASV-C is located at the parasite surface and secreted to the medium. Here we report that the expression of different TcTASV-C genes occurs simultaneously at the trypomastigote stage and while some secreted and parasite-associated products are found in both fractions, others are different. Secreted TcTASV-C are mainly shedded through trypomastigote extracellular vesicles, of which they are an abundant constituent, despite its scarce expression on culture-derived trypomastigotes. In contrast, TcTASV-C is highly expressed in bloodstream trypomastigotes; its upregulation in bloodstream parasites was observed in different T. cruzi strains and was specific for TcTASV-C, suggesting that some host-molecules trigger TcTASV-C expression. TcTASV-C is also strongly secreted by bloodstream parasites. A DNA prime—protein boost immunization scheme with TcTASV-C was only partially effective to control the infection in mice challenged with a highly virulent T. cruzi strain. Vaccination triggered a strong humoral response that delayed the appearance of bloodstream trypomastigotes at the early phase of the infection. Linear epitopes recognized by vaccinated mice were mapped within the TcTASV-C family motif, suggesting that blockade of secreted TcTASV-C impacts on the settlement of infection. Furthermore, although experimental and naturally T. cruzi-infected hosts did not react with antigens from extracellular vesicles, vaccinated and challenged mice recognized not only TcTASV-C but also other vesicle-antigens. We hypothesize that TcTASV-C is involved in the establishment of the initial T. cruzi infection in the mammalian host. Altogether, these results point towards TcTASV-C as a novel secreted virulence factor of T. cruzi trypomastigotes.